Improvement of mechanical properties of poly(lactic acid) by integration of sepiolite nanoclays: effect of ultrasonication on clay dispersion. (May 2014) - García, L.; Castell, P.; Peinado, V.; Muniesa, M.; Fernández, Á.
Abstract : Owing to the depletion of oil based resources, new environmentally friendly materials are in continuous development. Poly(lactic acid) (PLA), a thermoplastic polymer obtained from renewable resources, is being seriously considered as a replacement for petroleum based products. The aim of the present study is to enhance the mechanical properties of this biopolymer with the addition of a natural based filler, a functionalised sepiolite, and to ensure a good dispersion by applying ultrasonic waves throughout the compounding process. A good affinity between the polymer and the silicate filler is essential in the nanocomposite to attain the optimal reinforcement. Nanocomposites of PLA/sepiolite were processed by extrusion compounding containing different weight percentages of nanoreinforcement. An ultrasonic homemade device developed by the authors was coupled at die position and used to improve the dispersion of the nanoclays in the molten polymer. Nanocomposite materials were later injected to produce different specimens that were characterised. The effect on the mechanical properties of PLA reinforced with sepiolite was analysed by conducting flexural tests. Strain–stress curves were obtained, and their stiffness and toughness were compared for the different specimens. Micrographs (SEM) were examined to demonstrate the effectiveness of using ultrasounds to improve the dispersion of the nanoclays within the polymeric matrix. Viscosity under low shear rates was measured with a rotational parallel plate rheometer in order to monitor the changes induced on the rheological behaviour of the composites. It was demonstrated that the application of ultrasonic waves in composite compounding improves nanoclay dispersion, which results in an enhancement of the reinforcement of the fillers and decreases the viscosity of the composites during the process. These effects become more significant for high loads of reinforcement, especially for 10 wt-% sepiolite specimens.